2018
DOI: 10.1108/jfmm-12-2016-0115
|View full text |Cite
|
Sign up to set email alerts
|

Tracing brand constellations in social media: the case of Fashion Week Stockholm

Abstract: Purpose The purpose of this paper is to explore the effects of fashion weeks on brand constellations of participating fashion companies in social media. Design/methodology/approach The study analyses how brand constellations take form for seven Swedish fashion companies before, during and after Fashion Week Stockholm. In total, 3,449 user-generated contents referring to the sampled brands were collected and analysed. Findings On average, brand constellations of participating companies are increasingly inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Because of that, the fashion industry is one of the sectors with a widely integrated social network system. Customers are always exposed to new collections and trends through social media, who may become collaborators or observers than just mere consumers as they gain more knowledge and information (Geissinger and Laurell, 2018). Avid social network users usually have their designated online space to share information and create their system of WOM publicly.…”
Section: Conceptual Model and Research Hypothesesmentioning
confidence: 99%
“…Because of that, the fashion industry is one of the sectors with a widely integrated social network system. Customers are always exposed to new collections and trends through social media, who may become collaborators or observers than just mere consumers as they gain more knowledge and information (Geissinger and Laurell, 2018). Avid social network users usually have their designated online space to share information and create their system of WOM publicly.…”
Section: Conceptual Model and Research Hypothesesmentioning
confidence: 99%
“…Marco Brambilla et al [3] worked on the effect of social media on the Milan Fashion Week, investigating Instagram posts and responds of brand followers, also concluding that brands could be subdivided in four categories with respect to social media. Geissinger and Laurell [4] studied the impact of social media on the Stockholm fashion week, observing social behavior of Sweden during the fashion week by choosing seven brands and investigated the constellation of participating companies. They concluded that social media increasingly reached consumer realm.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The second approach includes emerging research which leverage on secondary data readily available among social media. For example, Geissinger and Laurell (2018) captured 3,449 user-generated interactions among seven datasets to examine the formation of fashion brand constellations during Stockholm's fashion week using the Lissly monitoring tool. Subsequently, they used content analysis to identify and map references to fashion brands for each respective dataset.…”
Section: Social Media Based Sna In Fashionmentioning
confidence: 99%
“…Social media is increasingly recognized as a rich data source through which tech savvy fashion brands pursue marketing strategy including building customer relationships, responding to market changes, promoting brands, creating viral marketing and ultimately capturing a larger audience (Mohr, 2013;Geissinger and Laurell, 2018;Nash, 2019).…”
Section: Introductionmentioning
confidence: 99%